Dynamic Interaction Between Mucosal Immunity and Microbiota Drives Nose and Pharynx Homeostasis of Common Carp (Cyprinus carpio) After SVCV Infection - Wu, Zheng-Ben; Meng, Kai-Feng; Ding, Li-Guo; Wu, Sha; Han, Guang-Kun; Zhai, Xue; Sun, Ru-Han; Yu, Yong-yao; Ji, Wei; Xu, Zhen (Frontiers in Immunology, 2021)
The crosstalk between the immune system and microbiota drives an amazingly complex mutualistic symbiosis. In mammals, the upper respiratory tract acts as a gateway for pathogen invasion, and the dynamic interaction between microbiota and mucosal immunity on its surface can effectively prevent disease development. However, the relationship between virus-mediated mucosal immune responses and microbes in lower vertebrates remains uncharacterized. In this study, we successfully constructed an infection model by intraperitoneally injecting common carp (Cyprinus carpio) with spring viremia of carp virus (SVCV). In addition to the detection of SVCV in the nose and pharynx of common carp, we also identified obvious histopathological changes following viral infection. Moreover, numerous immune-related genes were significantly upregulated in the nose and pharynx at the peak of SVCV infection, after which the expression levels decreased to levels similar to those of the control group. Transcriptome sequencing results revealed that pathways associated with bacterial infection in the Toll-like receptor pathway and Nod-like receptor pathway were activated in addition to the virus-related Rig-Ⅰ-like receptor pathway after SVCV infection, suggesting that viral infection may be followed by opportunistic bacterial infection in these mucosal tissues. Using 16S rRNA gene sequencing, we further identified an upward trend in pathogenic bacteria on the mucosal surface of the nose and pharynx 4 days after SVCV infection, after which these tissues eventually reached new homeostasis. Taken together, our results suggest that the dynamic interaction between mucosal immunity and microbiota promotes the host to a new ecological state.